INNOVATIVE STRATEGIES FOR EXPANDING STUDENTS’ VOCABULARY IN ENGLISH LANGUAGE CLASSES - Urinboyeva Dilrabo Olimjonovna (PEDAGOGS, 2025)
Abstract: This article explores interactive teaching techniques aimed at enhancing students’ vocabulary acquisition in English lessons. It emphasizes the importance of fostering independent thinking in learners and adopting modern educational methods. With English being a global communication tool, the necessity for students to master vocabulary through engaging strategies such as educational games has become essential. These methods not only support language development but also make learning enjoyable and memorable.